Comprehension of definite expressions by Mandarin-speaking children with suspected developmental language disorder (DLD) and children with autism spectrum disorder and language impairment (ALI) - Shasha An; Xiaowei He; Zhenghao Zhang (Glossa, 2024)
An increasing number of studies have shown that there is a subgroup inside children with autism spectrum disorder (ASD) who demonstrates impaired language profiles similar to children with developmental language disorder (DLD). As a discriminative marker, the determiner element is known to be particularly vulnerable in children with DLD, while less is known about the situation in children with ASD who show accompanying language impairment (ALI). The current study therefore investigates whether and how Mandarin-speaking children with DLD and children with ALI differ in their comprehension of definite expressions.To this end, 28 children with suspected DLD (Mean=5;2, SD=0;7), 32 children with ALI (Mean=5;3, SD=0;8), and 28 typically-developing children (Mean=5;3, SD=0;5) participated in the present study. Each child was experimentally tested on a series of picture judgment tasks, in which demonstrative-classifier NPs, third-person pronouns, and bare NPs were examined in the anaphoric environment.The findings showed that neither of the suspected DLD or ALI groups performed at target-like levels on the three definite expressions. This is most likely caused by the two groups’ immature knowledge of the syntax-semantics interface within the DP construction. Nonetheless, there remains a significant difference in the interpretation of third-person pronouns between the suspected DLD and ALI groups, with the worse performance in the latter group presumably resulting from co-morbid processing differences typical of individuals with ASD.